Breaking Wagner's Law: Which Countries Have the Most Limited Government?. (July 2022) - Murphy, Ryan H.
Which countries have the world's smallest and the world's largest governments? One-fifth of the Economic Freedom of the World index is a subindex scoring the size of government for countries across the world. This subindex is inclusive of the three dimensions of government spending, the top marginal tax rate, and the government ownership of the economy. Measured in this manner, the "smallest" governments are, generally, weak or fragile states. This paper recognizes Wagner's law, the empirical regularity that wealthier countries tend to spend more as a percentage of gross domestic product (GDP). It then performs a novel adjustment to the size of government data to account for Wagner's law, re-scores and re-ranks the countries, and explores the results.